Changes in serum cardiac troponins following a 21-km run in junior male runners - Tian, Y.; Nie, J.; Tong, T. K.; Cao, J.; Gao, Q.; Man, J.; Shi, Q.; Liu, W. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: This study was designed to examine the appearance and clearance characteristics of serum cardiac troponin T (cTnT) and I (cTnI) in junior runners after an exhaustive 21-km run. The dependence of the alternations of the cardiac troponins on the runners' training status reflected in training years, running ability and physiological profile at ventilatory threshold (Thvent) was also examined. Methods: Ten trained male adolescents (16.2±0.6 years) performed 21-km run and graded treadmill exercise with maximum effort on two different days. cTnT and cTnI immediately before and 2, 4 and 24 hours after exercise were measured in the 21-km trial. The parameters at Thvent including the running speed (Thvent-Speed) and V.O2 (Thvent-V.O2) were identified in the graded exercise trial. Results: Serum cTnT and cTnI in 6 of the 10 subjects measured 4 hours after the 21-km run were above the myocardial injury cutoffs of 0.03 and 0.09 ng.mL-1, respectively, but returned towards pre-exercise levels within 24 hours that were not in the same manner observed in the clinical situation of myocardial infraction. The 6 subjects' training status was generally lower than that of the rest 4. Further, subjects' 4-h serum cTnT and cTnI were negatively related to their training years, Thvent-Speed and Thvent-V.O2, and positively related to their personal best in half- and full-marathon races (r2>=36%, n=10). Conclusions: Such findings implied that clinicians based the diagnosis of long-distance run-induced myocardial infraction in novice junior runners upon the transient postexercise elevations of cardiac troponins alone should be with caution.